1983
DOI: 10.1128/iai.41.2.683-690.1983
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an antigen-specific immunoglobulin M antibody associated with acute Toxoplasma infection

Abstract: We used the protein gel transfer technique (Western blotting) to analyze the immune response to individual electrophoretically resolved Toxoplasma antigens. Toxoplasma antigens were fractionated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The array of resolved proteins was electrophoretically transferred to CNBr-activated filter paper and incubated with serum samples from patients with either acute or chronic Toxoplasma infections or with serum samples from seronegative controls. Serum immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Several years ago, Sharma et al reported three major antigens recognized by human IgG and IgM antibodies; they had molecular weights of 6,000, 22,000, and 32,000 (42). Other specificities were also described from 6,000 to 150,000 (14,28). Our study revealed higher molecular weights for both types of antibodies.…”
Section: Discussionsupporting
confidence: 68%
“…Several years ago, Sharma et al reported three major antigens recognized by human IgG and IgM antibodies; they had molecular weights of 6,000, 22,000, and 32,000 (42). Other specificities were also described from 6,000 to 150,000 (14,28). Our study revealed higher molecular weights for both types of antibodies.…”
Section: Discussionsupporting
confidence: 68%
“…The predicted molecular weights of these antigens showed slight variability according to the SDS-polyacrylamide gel used. Although the 32-35 kDa protein has been thoroughly investigated, the analysis of the low M r antigen has been limited because of the absence of monospecific antibodies (only total sera has previously been used; Erlich et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SAG1 is considered as an important candidate for the development of effective diagnostic reagents. Indeed, SAG1 is one of the first antigens recognized by Toxoplasma-specific IgM antibodies, who are one of the most important serological markers to identify acute toxoplasmosis [26], and is suitable for detecting anti-SAG1-specific IgG to determine immune status and susceptibility to Toxoplasma infection during pregnancy [27]. Furthermore, this molecule belongs also to a group of excreted-secreted antigens and has been evaluated as diagnostic marker that can be detected, by Western blot, in cerebrospinal fluids and serum of patients, during toxoplasmosis [28].…”
Section: Introductionmentioning
confidence: 99%